Motivasi, Norma Subjektif, dan Minat untuk Mengikuti Pendidikan Profesi Akuntan - Damayanti, Ida Ayu Putu; Widanaputra, Anak Agung Gde Putu (E-Jurnal Akuntansi, 2024)
This research aims to empirically prove the influence of career motivation, economic motivation, and subjective norms on interest in pursuing professional accounting education. The population is accounting graduates from the Faculty of Economics and Business, Udayana University. The sample was taken using the saturated sampling method and obtained 343 graduates as respondents. The analysis technique used is multiple linear regression. The results of the analysis show that career motivation, economic motivation, and subjective norms partially have a positive effect on interest in participating in PPAk. The implication of this research is to provide empirical support for the theory of planned behavior and motivation theory and can be a consideration for the Faculty of Economics and Business so that it can encourage the interest of students and graduates to take professional accounting education. Keywords: PPAk; Interests; Motivations; Subjective Norms